Biphasic changes in airway epithelial cell EGF receptor binding and phosphorylation induced by components of hogbarn dust. (26th November 2018) - Dodmane, Puttappa R.; Schulte, Nancy A.; Heires, Art J.; Band, Hamid; Romberger, Debra J.; Toews, Myron L.
Abstract: Purpose of the study: Workers in enclosed hogbarns experience an increased incidence of airway inflammation and obstructive lung disease, and an aqueous hogbarn dust extract (HDE) induces multiple inflammation-related responses in cultured airway epithelial cells. Epidermal growth factor receptor (EGFR) phosphorylation and activation has been identified as one important mediator of inflammatory cytokine release from these cells. The studies here investigated both early and late phase adaptive changes in EGFR binding properties and subcellular localization induced by exposure of cells to HDE.Materials and Methods: Cell surface EGFRs were quantified as binding to intact cells on ice. EGFR phosphorylation, expression, and localization were assessed with anti-EGFR antibodies and either blotting or confocal microscopy.Results: In BEAS-2B and primary human bronchial epithelial cells, HDE induced decreases in cell surface EGFR binding following both 15-min and 18-h exposures. In contrast, H292 cells exhibited only the 15-min decrease, with binding near the control level at 18 hr. Confocal microscopy showed that the 15-min decrease in binding is due to EGFR endocytosis. Although total EGFR immunoreactivity decreased markedly at 18 hr in confocal microscopy with BEAS-2B cells, immunoblots showed no loss of EGFR protein. HDE stimulated EGFR phosphorylation at both 15 min and 18 hr in BEAS-2B cells and primary cells, but only at 15 min in H292 cells, indicating that the different EGFR binding changes among these cell types is likely related to their different time-dependent changes in phosphorylation.Conclusions: These studies extend the evidence for EGFRs as important cellular targets for components of HDE and they reveal novel patterns of EGFR phosphorylation and binding changes that vary among airway epithelial cell types. The results provide both impetus and convenient assays for identifying the EGFR-activating components and pathways that likely contribute to hogbarn dust-induced lung disease in agricultural workers.